2004
DOI: 10.1093/ps/83.2.193
|View full text |Cite
|
Sign up to set email alerts
|

Overview of bone biology in the egg-laying hen

Abstract: In young pullets, long bones elongate by endochondral growth. Growth plate chondrocytes proliferate, then hypertrophy, and are replaced by osteoblasts that form a network of trabecular bone. This bone is gradually resorbed by osteoclasts as the bone lengthens. Long bones widen, and flat bones are formed, by intramembranous ossification in which cortical bone formation by osteoblasts in the periosteal layer is accompanied by osteoclastic resorption at the inner endosteal surface. Growth of structural trabecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
342
2
9

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 345 publications
(361 citation statements)
references
References 17 publications
8
342
2
9
Order By: Relevance
“…Moreover, we can infer that the similarity in the results obtained for bone characteristics of poultry depending on the lighting program effects is due to the absence of significant differences in feed consumption and egg production of poultry subjected to the lighting programs tested, since it has been reported that bone quality of laying hens depends upon the level of production (Silversides et al, 2006), intensity of bone resorption during the laying phase (Whitehead, 2004) and the calcium availability for eggshell formation (Fleming et al, 1998;Saunders-Blades et al, 2009).…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…Moreover, we can infer that the similarity in the results obtained for bone characteristics of poultry depending on the lighting program effects is due to the absence of significant differences in feed consumption and egg production of poultry subjected to the lighting programs tested, since it has been reported that bone quality of laying hens depends upon the level of production (Silversides et al, 2006), intensity of bone resorption during the laying phase (Whitehead, 2004) and the calcium availability for eggshell formation (Fleming et al, 1998;Saunders-Blades et al, 2009).…”
Section: Resultsmentioning
confidence: 76%
“…As laying hens age, there is a drop in the eggshell quality due to factors such as lower calcium retention and increased egg weight without increasing the shell weight, in addition to the common bone fragility at the end of the production cycle (Whitehead, 2004;Murata et al, 2009). Almeida Paz et al (2009) reported that regardless of the dietary calcium level, the laying hens mobilize the minerals from bones for eggshell formation, so bone quality reduces as they grow old.…”
Section: Introductionmentioning
confidence: 99%
“…This theory is not challenged by our results as no sex differences in pelvic morphology or energetics were found. Furthermore, the reduction in bone fracture resistance by the provision of calcium for egg production has also been suggested as a potential limitation on female terrestrial locomotion (Whitehead 2004;Lees et al 2011). It may be that female hindlimbs are weakened during, and just after the egg-laying period; however, this is likely to be of more importance to birds that spend more time locomoting terrestrially than the eiders.…”
Section: Discussionmentioning
confidence: 99%
“…심각할 경우 폐 사에 이르며 (Whitehead, 2004;Whitehead and Fleming, 2000), McCoy et al(1996)는 케이지에서 사육되던 중 폐사한 닭의 35%가 골다공증을 앓고 있었던 것으로 보고한 바 있다. 케 이지는 산란계가 날개를 펼칠 수 있을 만큼 공간이 넉넉하지 못하기 때문에 특히 날개 부근의 골격근이 매우 약해진다.…”
unclassified
“…그러나 일부 학자 들은 전자가 더 적합한 용어라고 주장하고 있다 (Lindberg and Nicol, 1997;van Liere and Wiepkema, 1992 (Rodenburg et al;2004;Rushen, 1982;Wood-Gush, 1971 Van Liere DW, Wiepkema PR 1992 Effects of long-term de-…”
unclassified